"Hic Facet Arthurus, Rex Quondam, Rexque Futurus:" The Analysis of Original Medieval Sources in the Search for the Historica King Arthur - Pevan, Erin (My University, 2007)
The stories of Arthurian literary tradition have provided our modern age with gripping tales of chivalry, adventure, and betrayal. King Arthur remains a hero of legend in the annals of the British Isles. However, one question remains: did King Arthur actually exist? Early medieval historical sources provide clues that have identified various figures that may have been the template for King Arthur. Such candidates such as the second century Roman general Lucius Artorius Castus, the fifth century Breton leader Riothamus, and the sixth century British leader Ambrosius Aurelianus hold high esteem as possible candidates for the historical King Arthur. Through the analysis of original sources and authors such as the Easter Annals, Nennius, Bede, Gildas, and the Annales Cambriae, parallels can be established which connect these historical figures to aspects of the Arthur of literary tradition.
Keywords: Arthur, King--Sources; Arthur, King--Historicity; Arthur, King--In literature